The Spirit Project: Strengthening the Capacities for Fostering Innovation Along Potato Value Chains in East Africa - Ritter, Enrique; Barrandalla, Leire; Malley, Zacharia; Ongol, Martin Patrick; Kaaya, Archileo; Ooko, George; Mínguez, María del Rosario; de Galarreta, Jose Ignacio Ruiz (Open Agriculture, 2017)
The project SPIRIT was conducted in Tanzania, Rwanda, Uganda and Kenya from 2012 to 2016 with the aim of increasing the contribution of agricultural science, technology and innovation to social development in East Africa. The project involved literature research, on-site visits and meetings with farmers, research institutions and stakeholders, information compilation, database establishment and a project webpage. A strategy with three main objectives and associated actions was implemented. The first objective focused on the improvement of scientific and technological knowledge of East African research organizations. For this, state-of-the-art research on innovative technologies and practices for enhanced product quality was assessed; a web-based knowledge-sharing platform was created; the “East Africa Potato Research and Knowledge Exchange Forum” was constituted and six meetings with visits were realized. The second objective focused on private and civil society actors and governmental services and aimed at reinforcing their capacities for generating and adopting innovative technologies and practices. Sixteen innovation sessions were conducted. Guidelines for enhancing product Open Agriculture. 2017; 2: 425–430quality along the potato value chain in East Africa were elaborated and disseminated. The third objective targeted governmental bodies with competences in policy-making for promoting changes in policies. Proposals for policy-makers were developed and transferred to relevant authorities.
Keywords: Capacity building; Potato quality; Knowledge Exchange Forum; Stakeholders